أثر آليات الحوكمة على أداء ومخاطر البنوك في القطاع المالي المصري - خلف، محمد سامي سلامة Khalaf, Mohammed Sami Salamah (جامعة الزقازيق - كلية التجارة, 2023)
يهدف البحث إلى دراسة واختبار أثر آليات الحوكمة الداخلية (حجم مجلس الإدارة واستقلاليته وقوة المدير التنفيذي والتنوع بين الجنسين وعدد اجتماعات المجلس) على أداء (معدل العائد على حقوق الملكية ومعدل العائد على الأصول) ومخاطر (مخاطر الائتمان ومخاطر السيولة) البنوك في القطاع المالي المصري. ومن خلال تحليل الدراسات السابقة تم اشتقاق فرضين رئيسين وخمسة فروض فرعية لكل منهما وتم استخدام أسلوب الانحدار المتعدد لاختبار فرضى الدراسة، وبالاعتماد على البرنامج الإحصائي EViews 10، وبالتطبيق على بيانات 15 بنكا في القطاع المالي المصري، وذلك خلال الفترة من عام 2013 إلى عام 2021. وتوصلت الدراسة إلى أن زيادة حجم مجلس الإدارة وزيادة عدد المديرين المستقلين يحسن من أداء البنوك في القطاع المالي المصري ويحد من مخاطرها، كما توصلت الدراسة إلى أنه على الرغم من أن زيادة قوة المدير التنفيذي (الازدواجية بين دور المدير التنفيذي ورئيس مجلس الإدارة) تحسن من معدل العائد على حقوق الملكية إلا أنه تزيد من مخاطر السيولة وهذ يوضح أهمية دراستنا حيث أنها تدرس أثر آليات الحوكمة على المخاطر والعائد معا. أما بالنسبة للتنوع بين الجنسين فقد توصلت الدراسة إلى أن وجود امرأة واحدة على الأقل في مجلس الإدارة يحسن من أداء البنك ولكن لا يؤثر على مخاطر البنك، وأخيرا، لم تجد الدراسة أي تأثير لعدد اجتماعات مجلس الإدارة على أداء ومخاطر البنوك في القطاع المالي المصري. وتسهم النتائج في فهم كيفية عمل آليات الحوكمة في البنوك المصرية وتأثيرها على أداءها ومخاطرها، مما قد يفيد المساهمين والمنظمين عند وضع القواعد والسياسات اللازمة لتحقيق الإصلاح المالي في البنوك من خلال التركيز على تشكيل مجلس الإدارة باعتباره أحد أهم آليات الحوكمة الداخلية التي تؤثر على أداء البنوك ومخاطرها. The research aims to study and test the impact of internal governance mechanisms (the size of the board of directors, its independence, the strength of the CEO, gender diversity, and the number of board meetings) on the performance of (return on equity ROE and return on assets ROA) and the risks (credit risk and liquidity risk) of banks in the Egyptian financial sector. Through the literature review, two main hypotheses and five sub-hypotheses were derived for each of them and we used Panel Regression to test the study hypotheses by relying on the EViews 10 statistical program, and by using data from 15 banks in the Egyptian financial sector, during the period from 2013 to 2021. The study concluded that increasing the size of the board of directors and increasing the number of independent directors improves the performance of banks in the Egyptian financial sector and reduces their risks. The study also found that although the increase in the power of the CEO (the duplication between the role of the CEO and the Chairman of the Board of Directors) improves ROE, it increases liquidity risk, and this illustrates the importance of our study as it studies the impact of governance mechanisms on risks and returns together. As for gender diversity, the study found that the presence of at least one woman on the board of directors improves the performance of the bank, but does not affect the risks of the bank. Finally, the study did not find any effect of the number of board meetings on the performance and risks of banks in the Egyptian financial sector. The results contribute to understanding how the governance mechanisms work in Egyptian banks and their impact on their performance and risks, which may benefit shareholders and regulators when setting the necessary rules and policies to achieve financial reform in banks by focusing on the formation of the board of directors as one of the most important internal governance mechanisms that effect on the performance and risks of banks.
Keywords: الحوكمة المالية -- الخدمات المصرفية -- الأداء المالي -- الأزمات المصرفية